Aplikasi Penjadwalan Tugas berbasis Mobile Device Didukung Google Task dan Google Drive - Elisa Yuni Anggraini; Adi Wibowo; Lily Puspa Dewi (Jurnal Infra, 2017)
As the increased of work productivity, many task scheduling applications are emerging. Each of Task scheduling applications has its own advantages to similar competitors. The applications helps the user to remember if one of task was approaching deadline, and to store activities’ data. However, to fulfil the task, we need a container to store important files in a safe place. In recent years, the use of Cloud Computing is growing because the data is safely stored. In the applications mentioned above, there is still no container to collect data to support of a task. Thus, in the process of a task requires a separate storage container of reminder apps such as flash, hard drive, or using cloud computing.These Scheduling Application is powered by Google Tasks and Google Drive. This app is designed to combine the reminder feature and supporting data storage task. The program uses Google Tasks as a container scheduling tasks and also use Google Drive as a storage container for supporting data. So this one application can covers the needs of users in the manufacturing operations tasks that are not found in other applications.